Penggambaran Sosok Pribumi dalam Film Bumi Manusia - Siti Nur Afani; Nani Kurniasari (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Native during the Dutch colonial period were often oppressed because their strata were low. The depiction of indigenous figures is depicted in the film Bumi Manusia. This study aims to determine the depiction of indigenous figures in the film Bumi Manusia. In this research, the researcher uses the theory of social reality construction, qualitative approach and semiotic analysis method from Charles Sanders Peirce. Researchers use the triangle of meaning, namely sign, object and interpretant. The results of this study found that there are five depictions of indigenous figures in the Bumi Manusia film, namely: representation of the role of indigenous children through objective and subjective factors, the desire of Minke to uphold the status of indigenous people so as not to be humiliated by foreign nations. Minke tried to fight the Dutch for the injustice that befell the natives. Films can construct the depiction of indigenous figures through every sign they use.